Diterpenoids from Zhumeria majdae roots as potential heat shock protein 90 (HSP90) modulators. (May 2021) - Zadali, Reza; Nejad-Ebrahimi, Samad; Hadjiakhoondi, Abbas; Fiengo, Lorenzo; D'Ambola, Massimiliano; De Vita, Simona; Tofighi, Zahra; Chini, Maria Giovanna; Bifulco, Giuseppe; De Tommasi, Nunziatina
Abstract: Four undescribed and 17 known diterpenoids were isolated from the roots of Zhumeria majdae Rech.f. & Wendelbo. Using 1D and 2D NMR spectroscopy, ECD spectroscopy, and HRESIMS data analysis, the structures of the undescribed compounds were elucidated. The anti-proliferative activity of isolated compounds was evaluated against HeLa and MCF7 cancer cell lines. The binding affinity of all compounds to HSP90, one of the targets for the modern anticancer therapy, was investigated using surface plasmon resonance. The results demonstrated that lanugon Q interacted with the chaperone. To explain its mechanism of action, experimental and computational tests were also conducted. Graphical abstract: Image 1 Highlights: Four undescribed diterpenoids, were isolated and elucidated from Zhumeria majdae . The absolute configuration of compounds has been established by circular dichroism. Lanugon Q exhibited a moderate tendency to interact with HSP90 and cytotoxicity activity against MCF 7 cancer cells. The results of western blotting and MTT assays were in agreement with SPR analysis. A molecular docking study was conducted to find possible interactions with HSP90.